Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Konkret MEDAROREMI terhadap Hasil Belajar IPAS pada Siswa Kelas VI SDN 1 Awirarangan - Gina Faojina; Dewi Eka Rani; Deby Nuraisyah; Ina Setiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low student learning outcomes in the Natural and Social Sciences (IPAS) subject are a common issue in elementary schools. This study aimed to determine the effect of the Problem-Based Learning (PBL) model, supported by the concrete learning aid MEDAROREMI (Media for the Impact of Earth's Rotation and Revolution), on the IPAS learning outcomes of Grade VI students at SDN 1 Awirarangan regarding Chapter 5, Sub-chapter B: The Impact of Earth's Rotation and Revolution. A quantitative research method employing a pre-experimental "one-group pretest-posttest" design was used. The population consisted of all students at SDN 1 Awirarangan, with a sample of 22 students from class VI-A selected via purposive sampling. The research instrument consisted of multiple-choice questions administered before and after the intervention. Data analysis included descriptive statistics, the Shapiro-Wilk normality test, and a paired-sample t-test for hypothesis testing. The results showed an increase in the average score from 59.09 (pretest) to 63.64 (posttest). The learning mastery rate rose from 36.4% to 45.5%. The average N-Gain score was 0.12, falling into the "low" category. The paired t-test yielded a t-value of 1.000 with a p-value of 0.329 (> 0.05), leading to the acceptance of the null hypothesis (H0). These findings indicate that the implementation of PBL supported by MEDAROREMI requires improvement and strengthened scaffolding in subsequent learning cycles. Keywords: Problem-Based Learning; MEDAROREMI; IPAS Learning Outcomes